SISTEM MONETER DALAM PERSPEKTIF EKONOMI ISLAM - IBRAHIM, ZAINI (Al Qalam, 2012)
In many economic literatures, economy is divided into two sectors, real sector which covers seroice market and goods market, and monetary sector which consists of money market and equity market. In a part of economic system, monetary that runs in a country will affect the economic rate. Monetary economy can be applied in a polity, called monetary policy. In a conventional discussion, a monetary policy is run in order to reach the increase of national income, to stabilize market price, and to control the inflation rate. To get the goal of that macro-economy, the interest rate is used, in which it becomes the weakness of conventional monetary system. The use of interest rate, furthermore, has caused the economic crisis, indeed global financial crisis. In term of new economic system needs, Islamic monetary system riflers a solution to overcome financial crisis. The riffered system is asset based transaction, free of interest, avoidance of transactions containing speculation (maisir) and uncertainty (gharar). Moreover, it also uses stable curencies, i.e. dinar and dirham. Keyword: Monetary system, interest rate, fiat monry, dinar, dirham.